Analisis Pengaruh Game E-Sport terhadap Aspek Kognitif Peserta Didik di SMAN 7 Balikpapan - Sani, Fadhlur; Iwandana, Dody Tri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The students in SMAN 7 Balikpapan were the subjects of this research. The research method employed was quantitative, with a sample consisting of members of the e-sports extracurricular activity at SMA 7 Balikpapan, known as